Riffat Hasan and the Quest for Gender Justice in Islam. - Bustomi Arisandi; Ahmed Murtada; Muhammad Imamul Muttaqin Arisandhi; Bahrul Ulum (Institut Bahri Asyiq Galis Bangkalan, 2025)
This article critically examines the concept of Qur'anic feminism through the lens of Riffat Hasan's views on gender equality. The discussion focuses on three key areas: first, Hasan's methodological approach to interpreting verses related to feminism; second, examples of his interpretation of these verses; and third, a critique of his interpretive methodology. Utilizing a descriptive qualitative approach rooted in library research, this study draws on various texts, manuscripts, and literature relevant to the topic. The findings reveal that: (1) Riffat Hasan adopts an empirical and idea-normative approach to interpret verses, aiming to challenge conventional readings; (2) Hasan's interpretation of the term Qawwamun in Surah al-Nisa' 4:34 suggests that the role of financial provider is not limited to men, thereby promoting a more equitable view of gender roles; and (3) Hasan’s interpretations have been critiqued for a lack of traditional exegetical training, leading his approach to sometimes be seen as overly textual and lacking depth in interpretive method. This study contributes to the ongoing discourse on gender equality within Islamic thought by analyzing Hasan’s work and its implications for modern interpretations of gender roles in the Qur'an.